2013
DOI: 10.1371/journal.pone.0070424
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of Global Genome Repair Do Not Respond to DNA Damaging Therapy but Correlate with Survival in Melanoma

Abstract: Nucleotide excision repair (NER) orchestrates the repair of helix distorting DNA damage, induced by both ultraviolet radiation (UVR) and cisplatin. There is evidence that the global genome repair (GGR) arm of NER is dysfunctional in melanoma and it is known to have limited induction in melanoma cell lines after cisplatin treatment. The aims of this study were to examine mRNA transcript levels of regulators of GGR and to investigate the downstream effect on global transcript expression in melanoma cell lines af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…To date, somatic mutations in XPC, DDB1 and DDB2 have rarely been reported in melanoma tumours. We reported that upstream regulators of GGR including p53, BRCA1 and PCNA are not responsible [ 18 , 23 , 29 ]. One possible mechanism affecting the expression of these genes is dysregulation of epigenetics such as DNA methylation.…”
Section: Introductionmentioning
confidence: 99%
“…To date, somatic mutations in XPC, DDB1 and DDB2 have rarely been reported in melanoma tumours. We reported that upstream regulators of GGR including p53, BRCA1 and PCNA are not responsible [ 18 , 23 , 29 ]. One possible mechanism affecting the expression of these genes is dysregulation of epigenetics such as DNA methylation.…”
Section: Introductionmentioning
confidence: 99%
“…Lower levels of NER post-platinum chemotherapy have been confirmed in ovarian cancer studies including low DDB2 in platinum-resistant ovarian cancer cell lines (Barakat et al 2010) and low XPA in platinum-resistant ovarian cancer tumours (Barakat et al 2010). In addition, low NER and platinum resistance has been reported for several other cancer types including non-small-cell lung cancer, gastric cancer, colorectal cancer and melanoma (Bowden et al 2010(Bowden et al , 2013. NER proteins are a promising area in biomarker development for platinum resistance for use in real-time clinical settings after platinum treatment has concluded.…”
Section: Figurementioning
confidence: 83%